Antibacterial and Antibiofouling Polymeric Membranes through Immobilization of Pyridine Derivative Leading to ROS Generation and Loss in Bacterial Membrane Integrity. Issue 26 (12th September 2017) - Samantaray, Paresh Kumar; Madras, Giridhar; Bose, Suryasarathi
Abstract: Porous, antibacterial and antibiofouling membranes were obtained from immiscible polymer blends using non‐solvent induced phase separation. Both antibacterial and antibiofouling was mediated by immobilizing quaternized pyridine derivative on the porous membranes. This was manifested by assessing the metabolic content leakage (K + ions and nucleic acid) monitored at different time intervals when the membranes were in contact with E.coli (gram negative) and S.aureus (gram positive). Further, the hydrophilic nature of the pyridine derivative led to antibiofouling nature. The hierarchical porous 'finger‐like' morphology was confirmed by Scanning electron Microscopy. The trans‐membrane flux was measured using a cross‐flow flux setup. A quantitative study of the antibacterial activity was carried out using a standard plate count method. The modified membranes showed 3‐log and 2‐log reduction in E. coli and S. aureus respectively in 2 h and 7‐log fold reduction in both bacterial strains in 24 h. The oxidative stress generated by the pyridine derivative on both the bacterial strains was assessed by measuring the Reactive Oxygen Species (ROS). The ROS was significantly higher in case of modified membranes which supported the biocidal nature of the pyridine derivative. The antifouling study was carried out by using BSA (Bovine serum albumin) as a model biofoulant. The flux recovery ratio was significantly higher in case of modified membranes. Abstract : The pyridine based QAC membranes exhibited high trans‐membrane flux of 885.73 ± 44.9 LMH (L/m 2 /h) and excellent antibacterial activity by mediating ROS and inducing contact based killing resulting in 3‐log reduction in E.coli (99.95% bacterial reduction) and 2‐log reduction in S.aureus (99.57% bacterial reduction) in 2 h and a 7‐log reduction in both strains in 24 h. In addition, the modified membranes exhibited excellent fouling resistance against bovine serum albumin and effective flux recovery of 81.28 ± 0.02% at 0.2 MPa